Penggunaan Google Jamboard Dalam Pembelajaran Online Terhadap Motivasi Belajar Peserta Didik Pada Materi Arus Bolak Balik - Reni Musriyanti; Andri Suherman; Rahmat Fiman Septiyanto (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
This study aims to determine the effect of using Google Jamboard on the motivation of students in the Alternating Flow material. This research is quantitative research with an experimental method. The research design used is the Posttest–Only Controll Group Design. Media with Google Jamboard as the independent variable and student motivation as the dependent variable. The population of this study was all students in class XII IPA SMAS Yuppentek 1 in Tangerang City for the academic year 2020/2021. The sample for this study consisted of 2 classes, namely, class XII IPA 3 as the experimental class and class XII IPA 5 as the control class. The sampling technique was random sampling. Data collection techniques using Posttest and Learning Motivation Questionnaires to measure students' learning motivation and Observation Sheets for the implementation of learning. The results of this study showed the average value of the ability of students' learning outcomes in the experimental class was 80.56, with a very good category. The average value of students' learning motivation in the experimental class is 73.17, with a good category. Based on the results of the t-test on the two-party pretest averages that tcount < ttable with a total of 0.932 < 1.69, there is no difference in the ability of the experimental class and control class students on alternating current material. Based on the results of the T-test on the one-party posttest showing tcount > ttable with a total of 3.53 > 1.69, it was concluded that there was an increase in the ability of students who received learning using Google Jamboard media compared to students without using Google Jamboard media. The results of the T-test show that, on the one hand, the N-Gain score is tcount > ttable or 11.159 > 1.69, with the conclusion that the experimental class students' abilities are higher than the control class students' abilities on alternating current material. Based on the results of the study, it can be concluded that there is a positive effect of using Google Jamboard on students' learning motivation on alternating current material.